Analysis of the Role of Actors in Management of Village Funds in Bintuas Village, Natal District, Mandailing Natal Regency - Hardianto, Rino; Sihombing, Marlon; Humaizi, Humaizi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The role of community actors in the management of village funds is conducting village meetings (MusDes), which in the village meetings are planning for the management of village funds used for physical and non-physical development of the village. The role of village government actors in the village fund management process is involved starting from problem identification, planning, implementation and evaluation.Therefore, the village government must involve other community actors starting from problem identification to evaluating the management of the village funds, and if community actors are involved there will be a sense of care for the development generated from the village funds. the involvement of actors in the management of village funds is very necessary, not only involving village officials, in this case community actors are also very necessary because in this case they can build a better village in the future and community actors must be actively involved in managing the village funds. The type of research used is a qualitative approach with a descriptive method with the results of the study showing a lack of community involvement in the management of village funds and a lack of openness by village actors in running a village program and a lack of openness in conducting village deliberations (musdes).